2020
DOI: 10.3389/fmed.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Functional Roles and Therapeutic Potentials of Long Non-coding RNAs in Cholangiopathies

Abstract: Long non-coding RNAs (lncRNAs) are RNAs with lengths exceeding 200 nucleotides that are not translated into proteins. It is well-known that small non-coding RNAs, such as microRNAs (miRNAs), regulate gene expression and play an important role in cholangiopathies. Recent studies have demonstrated that lncRNAs may also play a key role in the pathophysiology of cholangiopathies. Patients with cholangiopathies often develop cholangiocarcinoma (CCA), which is cholangiocyte-derived cancer, in the later stage. Cholan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Up to date, accumulating evidences have suggested that miRNAs play important roles and might be regarded as a potential therapeutic target in regulating the progression and development of several liver diseases (13)(14)(15)(16). Previous reports have demonstrated that there were increased levels of miR-130a-3p in myocardial injury, and downregulation of miR-130a-3p could remarkably relieve hypoxia-induced inflammation and inhibit the expression of fibrosis-related protein (17).…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, accumulating evidences have suggested that miRNAs play important roles and might be regarded as a potential therapeutic target in regulating the progression and development of several liver diseases (13)(14)(15)(16). Previous reports have demonstrated that there were increased levels of miR-130a-3p in myocardial injury, and downregulation of miR-130a-3p could remarkably relieve hypoxia-induced inflammation and inhibit the expression of fibrosis-related protein (17).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Li et al could demonstrate an upregulation of the oncogenic lncRNA H19 in exosomes derived from cholangiocytes under pathological conditions in the bile acid, which demonstrates the possibility to use lncRNAs as biomarkers also in BTC [252]. A possible future therapeutic strategy for BTC might include the use of RNA interference substances against tumor-promoting lncRNAs or proteins that are essential for the lncRNA function [253,254]. The substance Patisiran represents a FDA-approved RNA-interfering treatment option for hereditary transthyretin amyloidosis and it will be interesting to see whether this concept can be translated into cancer research and RNA interfering drugs might be able to inhibit oncogenic lncRNAs [255].…”
Section: Discussionmentioning
confidence: 99%
“…The substance Patisiran represents a FDA-approved RNA-interfering treatment option for hereditary transthyretin amyloidosis and it will be interesting to see whether this concept can be translated into cancer research and RNA interfering drugs might be able to inhibit oncogenic lncRNAs [255]. On the contrary, the induction of tumor-suppressive lncRNAs might also represent a potential strategy against BTC [254]. As summarized in this review, lncRNAs are aberrantly expressed in BTC patient samples and are involved in diverse oncogenic processes in BTC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous abnormally expressing miRNAs are associated with HCC initiation and progression [ 76 , 77 ]. Various studies have exposed the biological roles of lncRNAs as regulators of transcription, modulators of mRNA processing, and organizers of nuclear domains [ 76 , 77 , 78 , 79 ]. Compared with linear RNAs, circRNAs are more stable to exonuclease and ribonuclease, with conserved structure and stable sequence and tissue specificity [ 78 , 79 ].…”
Section: Characteristics and Classification Of Rnasmentioning
confidence: 99%